Unity Development Cookbook real-time solutions from game development to AI - Buttfield-Addison, Paris; Manning, Jon; Nugent, Tim (O'Reilly Media, Incorporated, 2023)
Learn everything you need to know to use the powerful Unity engine to its full potential for 3D and 2D game development, simulation, artificial intelligence, and beyond. From the basics of scripting to techniques for interactivity, AI and behavior, animation, narrative, and networking, this flexible, mind-bogglingly popular engine is useful for anything that needs visuals and real-time simulation. With this thoroughly updated problem-solving cookbook, beginner and intermediate Unity developers will learn about the Unity engine through brief recipes that teach specific features of the software and scripting systems. You'll apply a collection of snippets of code to address common scenarios such as properly keeping score, accepting input, and sharing state over the network. This cookbook pinpoints the problem, sets out the solution, and discusses how to solve your problem in the best and most straightforward way possible. You'll find solutions for: 2D and 3D graphics Math, physics, and character control Animation and movement Behavior and AI Sound and music Narrative and dialogue Input and gameplay Scripting and user interface Simulation and synthetic data creation Networking and accessing web content Analytics and telemetry.